Multi-class urinary antibiotic exposure, dietary sources, and childhood overweight and obesity risk through lipid metabolic disruption: evidence from multicenter cohorts in China - Xinli Song; Jieyu Liu; Li Chen; Yi Zhang; Ruolin Wang; Jianuo Jiang; Lan Zhang; Yanle Xiong; Jingyang Su; Ziqi Dong; Yang Qin; Dengcheng Zhang; et al. (Environmental Pollution, 2026)

Fabrication of microwave-absorbing MFe2O4@sepiolite (M = Mn, Mn0.5Ni0.5, Ni) nanorods with enhanced catalytic performance for degradation and assessment of intermediate toxicity - Ruolin Ni; Lei Jiang; Jinhui Lin; Dan Wu; Keming Zhang; Lu Fu; Zhaohong Zhang; Fang Ma; Yongcai Zhang (Applied Clay Science, 2026)

Activation-free hydrogen release and uptake in MgH2 enabled by flower-shaped NiMn bimetallic oxides - Yi Chen; Yunlong Zhang; Ruolin Li; Xiaojiang Hou (Chemical Engineering Journal, 2026)

Intercropping with alfalfa or soybean alleviates the continuous cropping obstacles of yam by altering the rhizosphere community and its metabolites - Pengfei Zhang; Wanghui Guan; Lili Han; Xiaoli Hu; Ailing Xu; Ruolin Wang; Xiaomin Wang (Rhizosphere, 2026)

Life-time levonorgestrel exposure causes intergenerational alterations of the thyroid-catecholaminergic–GABAergic functional network in zebrafish (Danio rerio) - Xing Hu; Qianlin Cai; Junhao Wu; Meixin Ye; Jinlin Yang; Hao Huang; Weiyi Liang; Yutong Zhang; Ruolin Shi; Yazi Liu; Liping Hou; Diyun Chen (Environmental Research, 2026)

Self-assembled carrier-free Cur@EGCG-Cu rescue inflammatory senescence and restore autophagy in tendinopathy - Yu Zhang; Qiqi Lou; Ran Yang; Xiang Li; Xiangkai Kong; Ruolin Cui; Ni Ni; Lilun Jin; Weiran Teng; Ping Gu (Chemical Engineering Journal, 2026)

Dissecting the genetic architecture of silique-related traits in rapeseed (Brassica napus L.) through genome-wide association studies and transcriptome analysis - Cuiping Zhang; Guangze Li; Ruolin Gong; Yunfei Zhang; Pan Lu; Chunyan Dai; Niannian Fan; Wu Yao; Xue Shi; Jungang Dong; Jihong Hu (Theoretical and Applied Genetics, 2026)

CeO2 nanoparticles-embedded hierarchical porous C/SiO2 for efficient catalytic amine regeneration in CO2 capture - Ling Liu; Yunrong Zhang; Yingying Zhang; Qi Dong; Yanyang Xue; Wanyi Ding; Fei Yang; Guo-Jun Kang; Ruolin Cheng; Shi-Jian Lu (Journal of Environmental Chemical Engineering, 2026)

Untargeted metabolomics analysis of foxtail millet fermented with Pleurotus geesteranus: Insights into the nutritional and antioxidant profiles - Tong Lin; Ziwei Zhang; Ruolin Shi; Gongjian Fan; Chunyan Xie (Food Chemistry, 2026)

A mutation in CsBRP1, encoding a PHD-type domain-containing protein, causes semi-dwarfism in cucumber (Cucumis sativus L.) - Xiaoxu Han; Juan Yin; Xueying Jiao; Ruolin Hu; Yingjie Zhang; Fahang Chen; Biao Dong; Chunyan Cheng; Yuhui Wang; Chunhua Wang; Ji Li; Tao Wu; et al. (Theoretical and Applied Genetics, 2026)

Biocontrol of Apple Valsa Canker by Bacillus sp. H12 and modulation of the apple seedlings microbiome - Ling Sun; Jianxin Gao; Yawen Tan; Yiting Xia; Ruolin Wang; Ruiqi Liu; Xinmei Zhang; Xia Yan; Lili Huang (Pesticide Biochemistry and Physiology, 2026)

A regulatory biomimetic nanoparticle targeting senescent glioma cells for BNCT treatment - Qi Dai; Zhicheng Zhang; Zhiqing Ben; Xiaoyan Sun; Yufan Yang; Yaxin Qin; QiYao Yang; Xiaoyan Bao; Linjie Wu; Ruolin Jiang; Xin Tan; Xufang Ying; et al. (Chemical Engineering Journal, 2026)

Co-modulation of overall compressibility and conductive networks on individual sensing unit for high-performance flexible tactile sensors - Yifan Liu; Zheming Zhang; Xiao Xu; Fengming Hu; Ruolin Liu; Rongmei Wang; Ming Lei; Ziyi Dai; Bingpu Zhou (Chemical Engineering Journal, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Widespread decline of gross primary productivity due to compound heat and drought in the Wei river Basin, China - Guangpo Geng; Ruolin Zheng; Tiantian Deng; Lei Zhang; Yousheng Wang; Zuxin He (Theoretical and Applied Climatology, 2025)

Adsorption of chlorogenic acid in aqueous solution of Chrysanthemum morifolium (Chuju) by walnut shell-derived biochar - Ying Gao; Nan Zhang; Xinran Xu; Ruolin Zhang; Jiahang Liu; Zongyao Qian; Xuelian Wang; Yunbin Qin (Food Chemistry, 2025)

Urban electric vehicle infrastructure: Strategic planning for curbside charging - Ruolin Zhang; Eleftheria Kontou (Journal of Transport Geography, 2025)

Per- and polyfluoroalkyl substances and platelet-related hematotoxicity: An integrated study of in silico, toxicological, and population evidence - Dihui Xu; Jie Xiang; Ruolin Qin; Zhijian Chen; Xiaofeng Wang; Peiwei Xu; Yitao Pan; Xinhan Zhang; Yan Wang; Ping Cheng; Yuan Chen; Dandan Xu; et al. (Journal of Hazardous Materials, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

Meta-analysis of electro-Fenton degradation efficiency: Unraveling the impacts of process parameters and cathode materials - Jiawei Wang; Guangchao Shi; Ruolin Liu; Shuhan Liu; Yuhan Zhang; Jianwei Yu; Dan Wu (Journal of Water Process Engineering, 2025)

The environmental concentration of diethylstilbestrol and its structural analogues promote the conjugation transfer of ARGs through the pheromone effect - Panpan Yang; Xiaobo Yang; Feng Wang; Rumeng Li; Man Zhang; Jingxue Qian; Ruolin Hao; Zhiqiang Shen; Jingfeng Wang; Lijuan Zhang; Zhigang Qiu; Yanhua Cao (Journal of Hazardous Materials, 2025)

Mitoquinone mesylate promotes oocyte maturation and subsequent embryonic development by regulating oxidative stress in Tibetan sheep - Bozhen Ji; Chengtu Zhang; Ruolin Zhao; Yifan Pan; Hong Wu; Yongzhong Chen; Ying Wu; Ru Meng; Yingbing Zhang; Yujie Tang; Jianmin Su (Animal Reproduction Science, 2025)

Investigating the cooling effect of urban lakes from the perspective of their characteristics and surrounding landscapes: A case study of 82 urban lakes in China - Ruolin Huang; Hao Hou; Jiahui Li; Ronald C. Estoque; Yuji Murayama; Li Chen; Xinmin Zhang; Tangao Hu (Science of The Total Environment, 2025)

Lower toxicity of HFPO-DA compared to its predecessor PFOA to the earthworm Eisenia fetida: Evidence from oxidative stress and transcriptomic analysis - Ruolin Wu; Xiaole Wang; Jingwen Zhang; Chengbo Lu; Bing Li; Zhongkun Du; Jun Wang; Jinhua Wang; Yue Yang; Lusheng Zhu (Journal of Hazardous Materials, 2025)

Fluoroquinolone antibiotics trigger selective oxidation in the trace-Cu(II)/peroxydisulfate system: The synergistic effect of dual reactive sites in chemical structure - Jiahang Liu; Xiaoyang Li; Ruolin Lv; Yingying Chu; Mengying Qian; Weiming Zhang (Journal of Hazardous Materials, 2025)

Analyzing water resources with sector characteristics in Fujian Province utilizing S2-DR-BIMCCP model integrated with the Gini coefficient - Ruolin Bai; Lei Jin; Yurui Fan; Xi Zhang; Ruoyu Yin; Yi Wei (Journal of Cleaner Production, 2025)

Dracocephalum Moldavica L.-derived carbon dots for effective periodontitis treatment via reprogramming energy metabolism in macrophages - Bo Zhang; Ruolin Ding; Xi He; Yifei Li; Zhongshan He; Jie Fang; Mengran Guo; Xinchun Wang; Zhihe Zhao; Xiangrong Song (Chemical Engineering Journal, 2024)

Characterization of MKK family genes and their responses to temperature stress and Vibrio parahaemolyticus infection in noble scallop Chlamys nobilis - Yetao Zeng; Ruolin Jiang; Jingwen Deng; Dewei Cheng; Weili Wang; Jianming Ye; Cheng He; Chuanxu Zhang; Hongkuan Zhang; Huaiping Zheng (Marine Environmental Research, 2024)

Correction: Sustained antigens delivery using composite microneedles for effective epicutaneous immunotherapy - Erkang Zhang; Binghui Zeng; Ruolin Song; Lu Yao; Huilian Che (Drug Delivery and Translational Research, 2024)

Association of the external environmental exposome and obesity: A comprehensive nationwide study in 2019 among Chinese children and adolescents - Li Chen; Yang Qin; Yi Zhang; Xinli Song; RuoLin Wang; Jianuo Jiang; Jieyu Liu; Tongjun Guo; Wen Yuan; Zhiying Song; Yanhui Dong; Yi Song; et al. (Science of The Total Environment, 2024)

Differentiated impacts of short-term exposure to fine particulate constituents on infectious diseases in 507 cities of Chinese children and adolescents: A nationwide time-stratified case-crossover study from 2008 to 2021 - Li Chen; Wen Yuan; Mengjie Geng; Rongbin Xu; Yi Xing; Bo Wen; Yao Wu; Xiang Ren; Yue Shi; Yi Zhang; Xinli Song; Yang Qin; et al. (Science of The Total Environment, 2024)

Association of maternal blood high-mobility group box 1 levels and adverse pregnancy outcomes: A systematic review and meta-analysis - Liping Xue; Ruolin Chen; Ying Liu; Peiguang Niu; Jintuo Zhou; Jinhua Liu; Jinhua Zhang; Huajiao Chen (Reproductive Biology, 2024)

Sono-assembly of ellagic acid into nanostructures significantly enhances aqueous solubility and bioavailability - Wei Gu; Ruolin Kong; Shuyang Qi; Xuxi Cheng; Xuyi Cai; Ziyun Zhou; Shunan Zhang; Hongyu Zhao; Jinyun Song; Qinglian Hu; Huiwen Yu; Huangjin Tong; et al. (Food Chemistry, 2024)

Influence of elevated temperature on the species and mobility of chromium in ferrous sulfate-amended contaminated soil - Ruolin Zhao; Xinqing Zhang; Yiwen Zhou; Jining Li; Binglin Guo; Keishi Oyama; Chiharu Tokoro (Journal of Environmental Management, 2024)

Oxidation of emerging contaminants by S(IV) activated ferrate: Identification of reactive species - Yingying Chu; Mujian Xu; Xiaoyang Li; Junhe Lu; Zhichao Yang; Ruolin Lv; Jiahang Liu; Lu Lv; Weiming Zhang (Water Research, 2024)

TRPA1-PI3K/Akt-OPA1-ferroptosis axis in ozone-induced bronchial epithelial cell and lung injury - Jiali Weng; Qi Liu; Chenfei Li; Yi Feng; Qing Chang; Meiqin Xie; Xiaohui Wang; Mengnan Li; Hai Zhang; Ruolin Mao; Na Zhang; Xiaohua Yang; et al. (Science of The Total Environment, 2024)

Responses of plant immune system and rhizosphere soil microbiome to the elicitor BAR11 in Arabidopsis thaliana - Ruolin Wang; Yu Wang; Dandan He; Tiecheng Shi; Yanan Zhang; Shang Liu; Xia Yan; Lili Huang (Science of The Total Environment, 2024)

Drought propagation characteristics across China: Time, probability, and threshold - Guangpo Geng; Bao Zhang; Qian Gu; Zuxin He; Ruolin Zheng (Journal of Hydrology, 2024)

Exploring the associations between phthalate exposure and cardiometabolic risk factors clustering among children: The potential mediating role of insulin-resistant-related genes DNA methylation - Jieyu Liu; Jieyun Song; Di Gao; Yanhui Li; Tongjun Guo; Wen Yuan; Manman Chen; Li Chen; Yi Zhang; Qi Ma; Mengjie Cui; Xinli Song; et al. (Journal of Hazardous Materials, 2024)

The impact of water quality on the formation of halogenated benzoquinones and the adsorption efficiency by activated carbon - Yongjing Wang; Song Gao; Xinyu Yan; Songtao Wang; Ruolin Zhang; Yan Zhou; Lianhai Ren; Cheng Li (Journal of Environmental Sciences, 2024)

Clinical Indicators of Hepatotoxicity in Newly Diagnosed Acute Promyelocytic Leukemia Patients Undergoing Arsenic Trioxide Treatment - Zhuo Zhang; Shunji Zhang; Fan Zhang; Qian Zhang; Hong Wei; Ruolin Xiu; Yanhong Zhao; Meijuan Sui (Biological Trace Element Research, 2024)
Arsenic trioxide (ATO)-induced hepatotoxicity is often observed in acute promyelocytic leukemia (APL) patients and decreases therapeutic effect of ATO. Thus, concerns over hepatotoxicity have been raised. The aim of this study was to explore some noninvasive clinical indicators that can be used to guide the individualized application of ATO in the future. APL patients treated with ATO were identified retrospectively via electronic health records at our hospital from August 2014 through August 2019. APL patients without hepatotoxicity were selected as controls. The association between putative risk factors and ATO-induced hepatotoxicity was estimated with ORs and 95% CIs, which were calculated using the chi-square test. The subsequent multivariate analysis was performed using logistic regression analysis. In total, 58.04% of patients experienced ATO-induced hepatotoxicity during the first week. Elevated hemoglobin (OR 8.653, 95% CI, 1.339–55.921), administration of nonprophylactic hepatoprotective agents (OR 36.455, 95% CI, 7.409–179.364), non-single-agent ATO to combat leukocytosis (OR 20.108, 95% CI, 1.357–297.893) and decreased fibrinogen (OR 3.496, 95% CI, 1.127–10.846) were found to be statistically significant risk factors for ATO-induced hepatotoxicity. The area under the ROC curve values were 0.846 for “overall ATO-induced hepatotoxicity” and 0.819 for “early ATO-induced hepatotoxicity.” The results revealed that hemoglobin ≥ 80 g/L, nonprophylactic hepatoprotective agents, and non-single-agent ATO and fibrinogen < 1 g/L are risk factors for ATO-induced hepatotoxicity in newly diagnosed APL patients. These findings can enhance the clinical diagnosis of hepatotoxicity. Prospective studies should be performed in the future to validate these findings.

An Underwater Image Restoration Deep Learning Network Combining Attention Mechanism and Brightness Adjustment - Jianhua Zheng; Ruolin Zhao; Gaolin Yang; Shuangyin Liu; Zihao Zhang; Yusha Fu; Junde Lu (Journal of Marine Science and Engineering, 2023)
This study proposes Combining Attention and Brightness Adjustment Network (CABA-Net), a deep learning network for underwater image restoration, to address the issues of underwater image color-cast, low brightness, and low contrast. The proposed approach achieves a multi-branch ambient light estimation by extracting the features of different levels of underwater images to achieve accurate estimates of the ambient light. Additionally, an encoder-decoder transmission map estimation module is designed to combine spatial attention structures that can extract the different layers of underwater images’ spatial features to achieve accurate transmission map estimates. Then, the transmission map and precisely predicted ambient light were included in the underwater image formation model to achieve a preliminary restoration of underwater images. HSV brightness adjustment was conducted by combining the channel and spatial attention to the initial underwater image to complete the final underwater image restoration. Experimental results on the Underwater Image Enhancement Benchmark (UIEB) and Real-world Underwater Image Enhancement (RUIE) datasets show excellent performance of the proposed method in subjective comparisons and objective assessments. Furthermore, several ablation studies are conducted to understand the effect of each network component and prove the effectiveness of the suggested approach.

Addressing challenges of an ageing population by rationally forecasting travel behaviours of the elderly: a case study in China - Xuesong Feng; Zhibin Tao; Lukai Zhang; Ruolin Shi (Environment, Development and Sustainability, 2023)

Selective fabrication of hydrophilic BiOCl deposition layer on bismuthinite surface for efficient molybdenite/bismuthinite separation - Shangyong Lin; Hongliang Zhang; Xiangsong Meng; Ruolin Wang; Wei Sun; Haisheng Han; Chenyang Zhang (Minerals Engineering, 2023)

TRIM21 of Micropterus salmoides exerts antiviral roles against largemouth bass ulcer syndrome virus - Zichao Peng; Caiyun Zhang; Baojie Yin; Yange He; Wenxian Li; Jinchao Wang; Jiaxin Xiao; Kaisong Peng; Chuanhe Bao; Ruolin Zhu (Fish & Shellfish Immunology, 2023)

An autocatalytic Fe(III)/H2O2 Fenton-like process triggered by tetracycline: The overlooked effect of quinone intermediates - Jiahang Liu; Xiaoyang Li; Yingying Chu; Ling Yuan; Ruolin Lv; Weiming Zhang (Chemical Engineering Journal, 2023)

Depression performance and mechanism of a novel reagent (Pb-starch) for calcite: Experimental and DFT study - Ruolin Wang; Hongliang Zhang; Wenjuan Sun; Haisheng Han (Minerals Engineering, 2023)

Conversion of agricultural waste to porous hydrochar for non-metallic activation of persulfate to phenol degradation via non-radical-dominated processes: Singlet oxygen and electron transfer - Jianhua Qu; Wanying Tong; Jun Zhang; Kaiyin Ye; Linsong Xiang; Ruolin Li; Di Wang; Zihe Chen; Qi Hu; Guangshan Zhang; Lei Wang; Ying Zhang (Journal of Cleaner Production, 2023)

Electric vehicle community charging hubs in multi-unit dwellings: Scheduling and techno-economic assessment - Ruolin Zhang; Noah Horesh; Eleftheria Kontou; Yan Zhou (Transportation Research Part D: Transport and Environment, 2023)

Electronic nose application for detecting different odorants in source water: Possibility and scenario - Yongjing Wang; Xinyu Yan; Songtao Wang; Song Gao; Kai Yang; Ruolin Zhang; Mengshu Zhang; Moru Wang; Lianhai Ren; Jianwei Yu (Environmental Research, 2023)

Reproductive toxicity of microplastics in female mice and their offspring from induction of oxidative stress - Yingbing Zhang; Xiyue Wang; Yifan Zhao; Jianglin Zhao; Tong Yu; Yupei Yao; Ruolin Zhao; Ruiluan Yu; Jun Liu; Jianmin Su (Environmental Pollution, 2023)

Sustained antigens delivery using composite microneedles for effective epicutaneous immunotherapy - Erkang Zhang; Binghui Zeng; Ruolin Song; Lu Yao; Huilian Che (Drug Delivery and Translational Research, 2023)

Novel carbon-coated zirconium oxide nanocomposites enable ultrahigh oxidant utilization efficiency for selective degradation of organic contaminants - Xiaoyang Li; Jiahang Liu; Ruolin Lv; Yingying Chu; Lu Lv; Junhe Lu; Weiming Zhang (Chemical Engineering Journal, 2023)

Quantitative trait loci for rolled leaf in a wheat EMS mutant from Jagger - Ruolin Bian; Na Liu; Yuzhou Xu; Zhenqi Su; Lingling Chai; Amy Bernardo; Paul St. Amand; Allan Fritz; Guorong Zhang; Jessica Rupp; Eduard Akhunov; Katherine W. Jordan; et al. (Theoretical and Applied Genetics, 2023)

Let-7c-5p down-regulates immune-related CDCA8 to inhibit hepatocellular carcinoma - Wanjin Chen; Haibo Wang; Yuanlong Shen; Shouwen Wang; Deng Liu; Hongchuan Zhao; Guobin Wang; Fan Huang; Wei Wang; Ruolin Wu; Liujin Hou; Zhenghui Ye; et al. (Functional & Integrative Genomics, 2023)

Amorphous zirconium oxide activates peroxymonosulfate for selective degradation of organic compounds: Performance, mechanisms and structure-activity relationship - Xiaoyang Li; Ruolin Lv; Weiming Zhang; Mingyang Li; Junhe Lu; Yi Ren; Yue Yin; Jiahang Liu (Water Research, 2023)

An R2R3-MYB FtMYB11 from Tartary buckwheat has contrasting effects on abiotic tolerance in Arabidopsis - Qian Chen; Lu Peng; Anhu Wang; Lingzhi Yu; Yu Liu; Xinrong Zhang; Ruolin Wang; Xiaoyi Li; Yi Yang; Xufeng Li; Jianmei Wang (Journal of Plant Physiology, 2023)

Multi-Degree-of-Freedom for Underwater Optical Wireless Communication with Improved Transmission Performance - Anliang Liu; Ruolin Zhang; Bin Lin; Hongxi Yin (Journal of Marine Science and Engineering, 2022)
Underwater optical wireless communication (UOWC) has great potential to provide high-speed and intensive communications over short ranges underwater. However, the mobility of the UOWC system is limited by the strict alignment requirements between the transceivers. In this paper, a multi-degree-of-freedom (MDOF) UOWC system with high flexibility and improved transmission performance is proposed and experimentally demonstrated based on the off-the-shelf light-emitting diode (LED) source. A hardware pre-equalization circuit is employed at the transmitter to extend the modulation bandwidth from 5.03 MHz to 50 MHz. At the receiving end, a Fresnel lens array is constructed to achieve efficient convergence of multiple incident optical signals from different directions. To improve the underwater signal transmission quality, we designed an additional digital signal recovery module after the trans-impedance amplifier. Finally, an experimental system is established with a 460 nm blue LED. The communication reliability of the system is verified by the measurement of the eye diagram and the bit error rate of the recovered signal at the receiving end. The experimental results show that optical signals from three different incident directions with a maximum data rate of 100 Mbps are reliably transmitted over a 1.2-m-long water tank using the non-return-to-zero on-off-keying modulation format.

Variation in the attached community structure and function of artificial habitats during ecological succession: A case study of the artificial reef area in Bailong Pearl Bay, China - Ruolin Li; Yu Guo; Ankai Zhang; Shuo Zhang; Hui Zhang; Chuanxin Qin (Frontiers in Marine Science, 2022)
With the continuous development of ports, ship transportation, resource extraction and artificial habitat deployment, an increasing number of artificial structures have created new usable spaces for marine organisms, and the biological communities living on their surfaces have undergone ecological succession. However, related studies have ignored ecological functions, interspecific relationships, and stability in different successional stages. Based on traditional taxonomy, this study applied functional diversity, niche overlap and niche breadth indexes to compare the attached organisms on artificial reefs (ARs) with different construction times in Bailong Pearl Bay, Fangchenggang City, Guangxi Zhuang Autonomous Region, China. The change trends of richness, habitat resource supply, resource utilization degree and efficiency, and interspecific relationships during the succession process were analysed. The results indicated that richness increased with functional diversity. While the number of species increased, the attached organisms showed different functional characteristics, and the number of species with identical traits decreased. The attached community in the later stage of development had a higher degree of utilization of ecological space, more comprehensive and efficient utilization of effective resources, a stronger degree of complementarity of organismal niches, and weaker interspecific competition. In the early stage of the developmental process, the attached community was affected by more environmental factors and had very significant correlations with those factors. The combination of the niche overlap index and the niche breadth index indicated that the resource supply supporting the survival and development of the attached organisms on the ARs with earlier construction times may be greater. The decrease in the number of biomarkers, the similarity of biomarkers belonging to the same family, and the similarity of dominance alternation all indicated that during the process of long-term development and community succession, the organisms attached to the various parts of the ARs tended to become more similar.

New Insight Into the Mechanism of Ecological Effects of Artificial Habitats: Elucidating the Relationship Between Protists Associated With Artificial Reefs and Adjacent Seawater - Ruolin Li; Yu Guo; Chuanxin Qin; Shuo Zhang; Dongping Ji; Hui Zhang; Jing Wang; Naiqian Zhao (Frontiers in Marine Science, 2022)
Artificial habitat deployment can restore natural habitats or supplement existing natural habitats. The effect of resource proliferation and protection is obvious. However, few reports have addressed the biological community association between artificial habitats and adjacent environments. Here, Illumina sequencing of 18S rDNA was performed, and the diversity, community structure, and co-occurrence networks of protists in different layers of artificial reefs (ARs) and adjacent seawater (WAR) were described to verify that constructing ARs in Bailong Pearl Bay improves local spatial heterogeneity and functional diversity. In terms of the degree of species interaction, the protist communities were ranked as follows: surface and bottom of WAR > ARs and WAR > different layers of ARs. The α-diversity of protists associated with ARs and WAR decreased with an increase in depth. Protist diversity was greater in WAR than in ARs. β-Diversity analysis revealed significant differences in protist community structure between WAR and ARs ( P < 0.05), and the upper layers of ARs and the middle or bottom layers of ARs differed. The key topological features of protist networks showed more positive interspecific interactions in the AR-associated protist community, a higher degree of niche differentiation, and higher complexity and stability. The keystone protists in the bottom seawater layer displayed community functions that were biased toward initial fixation in the ocean carbon cycle. The AR-associated protist community tended to participate in carbon transfer in the food chain and decomposition and utilization of dissolved organic matter (DOM). This study revealed significant differences in protist community structure between ARs and the adjacent environment, and the ecological functions of the key phyla were found to be related. In conclusion, protist communities in WAR may provide food sources for AR-associated heterotrophic protists. A variety of key phyla associated with ARs have biological roles in the carbon pump via their ecological characteristics.

Effects of process factors on the performance of electrochemical disinfection for wastewater in a continuous-flow cell reactor - Che-Jen Lin; Ruolin Zhang; Scott A. Waisner; Tabish Nawaz; Lori Center; David B. Gent; Jared L. Johnson; Sabin Holland (Environmental Science and Pollution Research, 2021)

Effect of enhancers on the phytoremediation of soils polluted by pyrene and Ni using Sudan grass (Sorghum sudanense (Piper) Stapf.) - Xiaoyan Liu; Siyuan Shen; Xinying Zhang; Xintong Chen; Ruolin Jin; Xinyi Li (Environmental Science and Pollution Research, 2020)

NGF protects bone marrow mesenchymal stem cells against 2,5-hexanedione-induced apoptosis in vitro via Akt/Bad signal pathway - Qi Wang; Ruolin Chen; Cong Zhang; Inam-u-llah; Fengyuan Piao; Xiaoxia Shi (Molecular and Cellular Biochemistry, 2019)

Screening the diatom Nitzschia sp. re-mutated by 137Cs-γ irradiation and optimizing growth conditions to increase lipid productivity - Jia Feng; Jun Cheng; Ruolin Cheng; Chuanxi Zhang; Junhu Zhou; Kefa Cen (Journal of Applied Phycology, 2015)